Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Coklat Daun Kelor di Toko Akilah 2R Bengkulu - Helmarini Helmarini; Bella Dwi Meisyah (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Akilah 2R Bengkulu store is one part of the UMKM. Which is a trading business managed by an independent business entity or individual. Akilah 2R Bengkulu shop is a shop that sells various kinds of Bengkulu city specialties, one of which is Chocolate Leaf Moringa. The purpose of this study was to determine the effect of product quality on the purchasing decision of Moringa Leaf Chocolate at Akilah 2R Bengkulu Store. The results of the study stated that the quality of the Moringa Leaf Chocolate product as many as 35 respondents who answered the questionnaire very well, none of which was where the criteria were located at (81-100%) if the percentage was 0%, those who answered the questionnaire were good, namely 30 people were located in the criteria (61-100%). 80%) if the percentage is 0.86%, those who answer the questionnaire are quite good, namely as many as 5 people are located in the criteria (41-60%) if it is presented, it is 0.14%, and those who answer the questionnaire are not good, there is no where the criteria lies in (20 -40%) if the percentage is 0%. Meanwhile, for purchasing decisions, it is known that the purchasing decision of Moringa Leaf Chocolate at Akilah 2R Bengkulu Store as many as 35 respondents who answered the questionnaire did not exist in the criteria (81-100%) if it was presented at 0%, those who answered the questionnaire were satisfied that as many as 33 people were in the criteria. (61-80%) if the percentage is 0.94%, those who answer are quite satisfied, namely as many as 2 people are located at (41-60%) if the percentage is 0.06%, and those who answer are not satisfied there is no where the criteria lies in ( 20-40%) if the percentage is 0%. There is an influence on the quality of the Moringa Leaf Chocolate product on purchasing decisions at Akilah 2R Bengkulu Store. This is obtained from F arithmetic > F table (30.04 > 4.20) and the level of influence is 92.7%.